Analisis Penggunaan Proteksi Arus Lebih Pada Generator Studi Kasus PLTU Teluk Sirih: Analisis Penggunaan Proteksi Arus Lebih Pada Generator Studi Kasus PLTU Teluk Sirih - Saputra, Ramadian (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2023)
The generator is one of the main components in the Teluk Sirih PLTU as a producer of electricity that will be supplied to consumers. The generator itself is not spared from existing disturbances. One of the disturbances that can occur in a generator is an overcurrent disturbance caused by a short circuit. Therefore the generator must be given a protection, namely an overcurrent relay which is useful for giving a signal to the PMT to open the circuit. In this report, we will test the performance of the overcurrent relay installed on the generator by looking for settings based on a 3-phase short circuit fault in one of the bus areas. The data used is in the form of Generator, Transformer and Overcurrent Relay specification data. Then from the data a series will be made and simulated using the ETAP 19.0.1 application. Based on the simulation that has been carried out, it is found that the magnitude of the 3-phase short circuit fault current in the Bus 2 area is 41501 A. Meanwhile for the overcurrent relay setting, the relay current is 3.39 A, the set current in the relay setting is 5982.757 A and the time is 0.34 s with a CT ratio of 1600:1. The result obtained is that the relay works according to the existing settings when a fault occurs and instructs the PMT to open the circuit.